Virulence of Cholera Toxin Gene-Positive Vibrio cholerae Non-O1/non-O139 Strains Isolated From Environmental Water in Kolkata, India - Takahashi, Eizo; Ochi, Sadayuki; Mizuno, Tamaki; Morita, Daichi; Morita, Masatomo; Ohnishi, Makoto; Koley, Hemanta; Dutta, Moumita; Chowdhury, Goutam; Mukhopadhyay, Asish K.; Dutta, Shanta; Miyoshi, Shin-Ichi; et al. (Frontiers in Microbiology, 2021)
Cholera toxin (CT)-producing Vibrio cholerae O1 and O139 cause acute diarrheal disease and are proven etiological agents of cholera epidemics and pandemics. On the other hand, V. cholerae non-O1/non-O139 are designated as non-agglutinable (NAG) vibrios and are not associated with epidemic cholera. The majority of NAG vibrios do not possess the gene for CT (ctx). In this study, we isolated three NAG strains (strains No. 1, 2, and 3) with ctx from pond water in Kolkata, India, and examined their pathogenic properties. Strain No. 1 expressed enterotoxicity in the intestinal loop test of rabbit. However, the enterotoxicity of strains No. 2 and 3 was small and undetectable, respectively. In order to clarify the virulence properties of these strains, genome sequences of the three strains were analyzed. The analysis showed that there was no noticeable difference among three isolates both in the genes for virulence factors and regulatory genes of ctx. However, vibrio seventh pandemic island-II (VSP-II) was retained in strain No. 1, but not in strains No. 2 or 3. Furthermore, it was revealed that the genotype of the B subunit of CT in strain No. 1 was type 1 and those of strains No. 2 and 3 were type 8. Further examination showed that strain No. 1 expressed cytotoxicity. This indicated that strain No. 1 may possesses virulence factors to induce severe syndrome when the strain infects humans, and that some strains of NAG vibrio inhabiting pond water in Kolkata have already acquired virulence, which can cause illness in humans. There is a possibility that these virulent NAG vibrios, which have acquired genes encoding factors involved in virulence of V. cholerae O1, may emerge in various parts of the world and cause epidemics in the future.